Nanoparticles that do not adhere to mucus provide uniform and long-lasting drug delivery to airways following inhalation - Craig S. Schneider; Qingguo Xu; Nicholas J. Boylan; Jane Chisholm; Benjamin C. Tang; Benjamin S. Schuster; Andreas Henning; Laura M. Ensign; Ethan Lee; Pichet Adstamongkonkul; Brian W. Simons; Sho-Yu S. Wang; et al. (2017)
Mucoadhesive particles (MAP) have been widely explored for pulmonary drug delivery because of their perceived benefits in improving particle residence in the lungs. However, retention of particles adhesively trapped in airway mucus may be limited by physiologic mucus clearance mechanisms. In contrast, particles that avoid mucoadhesion and have diameters smaller than mucus mesh spacings rapidly penetrate mucus layers [mucus-penetrating particles (MPP)], which we hypothesized would provide prolonged lung retention compared to MAP. We compared in vivo behaviors of variously sized, polystyrene-based MAP and MPP in the lungs following inhalation. MAP, regardless of particle size, were aggregated and poorly distributed throughout the airways, leading to rapid clearance from the lungs. Conversely, MPP as large as 300 nm exhibited uniform distribution and markedly enhanced retention compared to size-matched MAP. On the basis of these findings, we formulated biodegradable MPP (b-MPP) with an average diameter of <300 nm and examined their behavior following inhalation relative to similarly sized biodegradable MAP (b-MAP). Although b-MPP diffused rapidly through human airway mucus ex vivo, b-MAP did not. Rapid b-MPP movements in mucus ex vivo correlated to a more uniform distribution within the airways and enhanced lung retention time as compared to b-MAP. Furthermore, inhalation of b-MPP loaded with dexamethasone sodium phosphate (DP) significantly reduced inflammation in a mouse model of acute lung inflammation compared to both carrier-free DP and DP-loaded MAP. These studies provide a careful head-to-head comparison of MAP versus MPP following inhalation and challenge a long-standing dogma that favored the use of MAP for pulmonary drug delivery.